DEVELOPING EFFECTIVE TEACHING STRATEGIES WITHIN THE CREDIT-MODULE SYSTEM (TAMADDUN NURI JURNALI, 2024)
This article explores the development of effective teaching strategies within the credit-module system aimed at increasing the didactic adaptation of young teachers in higher education. The characteristics and principles of the credit-module system were reviewed, and its modular structure and credit fund were emphasized. Explores the unique challenges young teachers face, such as managing diverse student cohorts and balancing workloads within a modular system.